Geoengineering Disinformation: Two Opposing Testimonies and the Stakes for Humanity - Hagen, Mark; Herndon, J. Marvin; Whiteside, Mark; Baldwin, Ian (Advances in Social Sciences Research Journal, 2024)
Covert military geoengineering operations have been ongoing for the better part of three decades. Civilian airlines based in NATO countries are part of this planetary operation. Its aim appears to be to warm the planet to gain access to the immense stores of hydrocarbons and strategically important minerals beneath polar ice. To keep the public from understanding what is going on, the governments involved, led by the U.S., have resorted to disinformation on a broad, no-holds-barred scale. Disinformation involves mixing truth with lies, half-truths with omitted truths, so that the public remains ignorant or misinformed, and thus disinclined to protest or otherwise intervene. Two long-term observers, one a geoengineering critic, the other a retired commercial airline pilot (and co-author of this article), provide differing testimony for the geoengineering holocaust.